Language Testing in the 'Hostile Environment': The Discursive Construction of 'Secure English Language Testing' in the UK. (11th May 2019) - Harding, Luke; Brunfaut, Tineke; Unger, Johann W
Abstract: In parallel with an increased focus on border security in immigration and citizenship policy in the UK (the so-called 'hostile environment' policy), Government-approved English language tests for visa and immigration purposes were officially labelled 'Secure English Language Tests' (SELTs) in 2010. The proximity of security concerns in language testing with broader national immigration policy objectives suggests a complex role for language tests as gatekeeping devices. This article draws on critical discourse studies to explore this issue. Documents provided in the 2014 tender round for selecting Secure English Language Tests (acquired through a Freedom of Information request) were analysed through a discourse-historical lens (Reisigl and Wodak 2016 ) to map salient topics and identify discursive strategies used to construct 'secure English language testing'. Findings show that security is a prominent topic in the tender; prospective bidders are required to meet detailed security requirements and to police subcontractors, and social actors, spaces, objects, policies and procedures are routinely described in securitized terms. Implications are drawn for understanding the role of language tests within broader securitization processes.